Development of an Innovative Cell Isolation Method for the Investigation of Breast Cancer Pathogenesis and Angiogenesis for Experimental In Vitro And In Vivo Assays - Weigand, Annika; Tasbihi, Kereshmeh; Strissel, Pamela; Strick, Reiner; Horch, Raymund E.; Boos, Anja (Handchirurgie, Mikrochirurgie, Plastische Chirurgie, 2017)
Background Breast cancer is the world's most common cancer among women. Autologous lipotransfer is increasingly used for breast reconstruction following surgical removal of the tumour. In cell-assisted lipotransfer, the transplant is enriched with stem cells from adipose tissue (ADSC). Despite positive clinical results, there are some concerns regarding oncological safety due to transplanted stem cells. To date there are only a few breast cancer studies using primary cells from the same patient to enable further investigation into the complexity of cell-cell interactions in breast cancer in an experimental setting.Materials and methodsWe performed literature research on the topic of autologous lipotransfer. 5 different cell types (epithelial, mesenchymal cells, ADSC, endothelial cells, endothelial progenitor cells) were isolated from mammary (carcinoma) tissue or blood and were subsequently characterised for gene and protein expression as well as functional properties. The arteriovenous (AV) loop model in the rat was evaluated as a possible in vivo model for breast cancer pathogenesis and angiogenesis in this study.ResultsThe literature provided evidence for an in-vitro interaction between ADSC and cells of the mammary (carcinoma) tissue. In some clinical studies, certain subgroups of patients appeared to be exposed to an increased risk of tumour recurrence after lipotransfer, but in most studies no correlation between lipotransfer and tumour recurrence was found. Different cell populations, which differed significantly in terms of surface markers, gene expression and functional properties, were isolated from tissue of the same patient. Axial vascularised tissue was successfully generated in the AV loop model.ConclusionIn this study we were able to isolate different cell populations from the same patient, which reflect the heterogeneity of the tumour tissue. This enables a precise analysis of cell-cell interactions and their effects on tumour angiogenesis and pathogenesis in breast cancer. In combination with the AV loop model, this offers new possibilities to generate vascularised mammary carcinoma tissue as well as healthy mammary gland tissue in vivo as an optimal model for the clinical setting.
EVALuna2:32854

Plasticity of patient-matched normal mammary epithelial cells is dependent on autologous adipose-derived stem cells - Kengelbach-Weigand, Annika; Tasbihi, Kereshmeh; Strissel, Pamela; Schmid, Rafael; Marques, Jasmin Monteiro; Beier, Justus; Beckmann, Matthias; Strick, Reiner; Horch, Raymund E.; Boos, Anja (Scientific Reports, 2019)
Due to the increasing clinical application of adipose-derived stem cells (ADSC), e.g. lipotransfer for breast reconstruction, this study aimed to gain novel insights regarding ADSC influence on breast tissue remodeling and determine patient-dependent factors affecting lipotransfer as well as begin to address its oncological risks. The ADSC secretome was analyzed from five normal breast reduction patients and contained elevated levels of growth factors, cytokines and proteins mediating invasion. ADSC/ADSC secretomes were tested for their influence on the function of primary mammary epithelial cells, and tumor epithelial cells using cell culture assays. ADSC/ADSC secretomes significantly stimulated proliferation, transmigration and 3D-invasion of primary normal and tumor epithelial cells. IL-6 significantly induced an EMT and invasion. The ADSC secretome significantly upregulated normal epithelial cell gene expression including MMPs and ECM receptors. Our study supports that ADSC and its secretome promote favorable conditions for normal breast tissue remodeling by changing the microenvironment. and may also be important regarding residual breast cancer cells following surgery.
CRIS-Team Scopus Importer:2019-08-06

Selinexor’s Immunomodulatory Impact in Advancing Multiple Myeloma Treatment - Tasbihi, Kereshmeh; Bruns, Heiko (Cells, 2025)
Despite the major advancements in the repertoire for multiple myeloma (MM) treatment, this disease remains a chronically progressive plasma cell malignancy. Drug resistance and high relapse rates complicate the extended treatment strategies. However, the tumor microenvironment (TME) in MM is decisive for the success of a therapy or relapse. Aiming to improve the outcome of relapsed and refractory MM patients, Selinexor has entered the drug arsenal of myeloma therapy through the implementation of a novel therapeutic approach by selectively inhibiting the nuclear export receptor Exportin-1 (XPO1). Selinexor leads to the inactivation of cancer-related proteins and induces apoptosis by disrupting the nucleocytoplasmic flow in myeloma cells. While this drug is selectively cytotoxic to neoplastic cells, Selinexor’s immunomodulatory impact on the TME is currently being investigated. The aim of this review was to elucidate Selinexor’s capacity to influence the cell interaction network of the TME from an immunological perspective. Deciphering the complex interplay of highly plastic immune cells provides a contribution to the molecular–biological exploration of disease initiation and progression in MM. Unraveling the novel therapeutic targets of the immunological TME and evaluating the advanced immunotherapeutic regimens implementing Selinexor will shape the future directions of immune-oncotherapy in MM.
CRIS-Team Scopus Importer:2025-04-18
Keywords: Exportin-1; immunotherapy; multiple myeloma; nuclear export; Selinexor; tumor microenvironment; XPO1; XPOVIO